(untitled) (Revue D’études Interculturelles De L’image, 2014)
With over 7,000 exhibitors from over 100 countries and circa 300,000 visitors each year the Frankfurt Book Fair is a playground for political, economic, and cultural imaginings, including many domestic and foreign places. The Book Fair is often conceived of and studied as a site of intercultural politics and commerce but has not yet fully been explored as a site of translation and translator’s agency. This essay offers critical reflections upon metaphors for the translator, arguing that a shift of the base metaphor in comparative literature studies of translation from conflict to friction could redirect interdisciplinary translation studies. I propose that the friction metaphor leads toward an appropriate balance between complex detail and ordering reduction of data that allows us to describe the intensity and the challenges of translation without recreating the old-established realities we already know.